Reexamining the Democratic Party in the Implementation of Indonesia’s General Elections - Dedi Kusuma Habibie; Herdin Arie Saputra; Sanny Nofrima; Dafrin Muksin (Journal of Local Government Issues (LOGOS), 2021)
Direct elections (Pilkada) are part of democracy; it shows a clear orientation, where the positioning and interests of the people are at the highest level in politics so far. This study aims to analyze some of the main problems in the implementation of regional elections in Indonesia. This type of research used in this research is qualitative research. Analyzes were performed using the Nvivo 12 plus software. In data collection, this research was conducted through literature studies or focused on secondary data in journals and well-known online media news. The result of this research is that the direct regional election cannot be separated from various problems, such as the size of political capital, the weak role of political parties, the existence of interests, oligarchs, political dynasties, money politics, and intimidation of state civil servants (ASN). Pilkada immediately seemed to be dominated by elite groups with established modalities not to provide public space to participate